We describe the implementation of modified initialization and load balancing methods during parallelization of search algorithms for solution of optimization problems on high performance computing structures. Most optimization problems in discrete mathema - Geoletsyan , Grigor H.; Geoletsyan, Hrant G. (Mathematical Problems of Computer Science, 2021)
We describe the implementation of modified initialization and load balancing methods during parallelization of search algorithms for solution of optimization problems on high performance computing structures. Most optimization problems in discrete mathematics related to applications in new research areas are NP-hard. Parallelization of search algorithms using static and dynamic load-balancing (distribution of computational resources) and their implementation on high performance computing structures, in particular, on computer clusters is an essential tool for obtaining effective solutions to such problems.